Overexpression of interleukin‐10 in engineered macrophages protects endothelial cells against LPS‐induced injury in vitro. Issue 3 (26th January 2022) - Yi, Lingxian; Weng, Tujun; Nie, Penghui; Zhu, Lin; Gao, Mingming; Jia, Hongxing; Yang, Shaohua; Li, Xiubin; Zhang, Luo; Xu, Ye; Ma, Penglin; Hu, Mei
Abstract : Endothelial dysfunction is a primary pathophysiological change in sepsis. Macrophages are known to interact with vascular endothelial cells during the development of sepsis. Recently, drug delivery based on engineered macrophages was reported as an alternative approach for the management of diseases. Interleukin‐10 (IL10) is a well‐known anti‐inflammatory cytokine, which reduces inflammation and inhibits dysfunction of endothelial cells caused by sepsis. It is currently poorly understood whether genetically modified macrophages with overexpression of IL10 are able to restore endothelial integrity and function at the cellular level. In this study, we used lentiviral vectors to construct RAW264.7 macrophages engineered to overexpress IL10 (IL10‐eM) and investigated the effects of the IL10‐eM supernatant on LPS‐induced endothelial dysfunction using a noncontact coculture system. We found that cotreatment with IL10‐eM supernatant significantly attenuates the effects of LPS‐induced dysfunction of endothelial cells, including endothelial inflammatory response, endothelial permeability, and apoptosis. In addition, we discovered that LPS‐induced downregulation of VE‐cadherin and high production of reactive oxygen species were significantly attenuated upon IL10‐eM exposure. Furthermore, upregulation of IL6, TNFα, and Bax was decreased after treatment of cells with IL10‐eM supernatant. These results demonstrated that supernatant from engineered macrophages genetically modified with IL10 can effectively protect endothelial cells against LPS‐induced dysfunction in vitro, suggesting that exosomes from such engineered macrophages may have therapeutic effects against sepsis. Abstract : Restoration of vascular endothelial cells (VECs) dysfunction might be a potential therapeutic strategy for sepsis. In the current study, we developed an engineered macrophage releasing IL10, and through a noncontact coculture system, demonstrated that supernatant from engineered macrophages overexpressing IL10 could significantly suppress LPS‐induced endothelial inflammatory response, restore endothelial integrity, and decrease the apoptosis of endothelial cells.